Metacognitive Strategies and Discipline and Self-Control among College Students: A Multi-trait, Multi-method Analysis - Hanzen Reyes (Southeast Asian Journal of Science and Technology, 2021)
Abstract – This study focused on the multi-trait, multi-method examination of metacognitive strategies and discipline and self-control and the three contexts: (a) family, (b) school, and (c) community.  The research objective of this study was to investigate whether students evaluate their decision making and problem solving strategies and plan and regulate actions differently in contexts such as family, school and community. The sample for this study comprised 198 college students recruited from one public university and two private universities at Metro Manila. In the MTMM analysis of this study, the correlations between the monotrait-heteromethod (domains) is relatively high, suggesting that regardless of contexts (domains), the trait values are consistent. This result may indicate that the measures are not specific to the context of family, school, and community. Apart from family, school, and community contexts, one recommendation is to use peer and workplace contexts to examine if students will decide on the proper course of action and prioritize tasks to achieve their desired end in mingling with friends or in work responsibilities differently in such contexts. Also, to further expound in determining the extent in which the youth accept and are aware of the roles they play and the tasks they perform in the context of development, self- efficacy for roles and tasks could be added to the variable. This is to investigate if college students perceive that they are confident in their ability to successfully plan and having a sense of whether their plans and strategies are working in attaining their goals differently in family, school, and community contexts.